Organizing and institutionalizing local sustainability : a design approach - Deslatte, Aaron ([New York?] : Cambridge University Press, 2023)
"Sustainability reflects perhaps the greatest combination of design problems facing local governments today. To look at the future, crises are everywhere, and they are contagious: climate change hastens pandemics and exacerbates systemic inequity. Yet, there is precious little theoretical or empirical consensus about how public managers should systematically address these challenges. This Element explores the role of public managers as designers. Drawing from systems-thinking and strategic management, a process-tracing methodology is used to examine three design processes whereby public managers develop strategies for adapting to climate change, build the requisite capabilities and evaluate outcomes. Across three cases, the findings highlight the role of managers as "design-oriented" integration agents and point to areas where additional inquiry is warranted"--
Introduction : Design processes in local sustainability -- Strategy assemblage : Designing conceptual futures in South Bend -- Recovery and realignment : Organizational capabilities and their codification in Bloomington -- Reverse-engineering performance : Outcome identification in Indianapolis -- Institutionalizing design processes : Challenges and future directions for managing city sustainability.
Includes bibliographical references.
Keywords: Local government -- Indiana; Sustainability -- Indiana; Organizational change -- Indiana; Strategic planning -- Indiana; Organizational learning -- Indiana; Performance -- Management